Neuropathic Injury–Induced Plasticity of GABAergic System in Peripheral Sensory Ganglia - Wang, Caixue; Hao, Han; He, Kaitong; An, Yating; Pu, Zeyao; Gamper, Nikita; Zhang, Hailin; Du, Xiaona (Frontiers in Pharmacology, 2021)
GABA is a major inhibitory neurotransmitter in mammalian central nervous system (CNS). Inhibitory GABAA channel circuits in dorsal spinal cord are the gate-keepers of the nociceptive input from the periphery to the CNS. Weakening of these spinal inhibitory mechanisms is a hallmark of chronic pain. Yet, recent studies suggest existence of an earlier GABAergic ‘gate’ within the peripheral sensory ganglia. In this study, we performed systematic investigation of plastic changes of the GABA related proteins in the dorsal root ganglion (DRG) in the process of neuropathic pain development. We found that chronic constriction injury (CCI) induced general downregulation of most GABAA channel subunits as well as the GABA producing enzyme, glutamate decarboxylase, consistent with the weakening of the GABAergic inhibition at the periphery. Strikingly, alpha5 GABAA subunit was consistently upregulated. Knock-down of alpha5 subunit in vivo moderately alleviated neuropathic hyperalgesia. Our findings suggest that while development of neuropathic pain is generally accompanied by weakening of the peripheral GABAergic system, alpha5 GABAA subunit may have a unique pro-algesic role and, hence, might represent a new therapeutic target.